Pengaruh Environmental, Social, and Governance terhadap Nilai Perusahaan dengan Inovasi Teknologi sebagai Variabel Moderasi: Studi pada Perusahaan Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2024 - Hanna Farida; Retno Yuni Nur Susilowati (International Forum of Researchers and Lecturers, 2026)
This study aims to examine the effect of Environmental Disclosure, Social Disclosure, and Governance Disclosure on firm value and to investigate the moderating role of technological innovation in Indonesian listed mining companies during the 2021–2024 period. This research employed a quantitative approach using secondary data obtained from annual reports and sustainability reports. The sample consisted of 26 mining companies selected through purposive sampling, resulting in 104 firm-year observations. Panel data regression combined with Moderated Regression Analysis (MRA) was employed to test the hypotheses. The findings reveal that Environmental Disclosure, Social Disclosure, and Governance Disclosure do not significantly affect firm value. Furthermore, technological innovation, proxied by intangible assets, does not moderate the relationship between ESG disclosure and firm value. These findings indicate that ESG information has not yet become a primary consideration for investors in valuing mining companies in Indonesia. Investors continue to prioritize financial performance indicators and industry prospects over sustainability-related disclosures. This study contributes to the ESG literature by examining the environmental, social, and governance dimensions separately rather than using a composite ESG score while incorporating technological innovation as a moderating variable, thereby providing a more comprehensive understanding of ESG disclosure and firm value in the Indonesian mining sector.